Physicochemical Quality Parameters at the Reception of the Honey Packaging Process: Influence of Type of Honey, Year of Harvest, and Beekeeper. (3rd May 2015) - Juan-Borrás, Marisol; Domenech, Eva; Conchado, Andrea; Escriche, Isabel
Abstract : The aim of this paper was to evaluate the influence of the type of honey, year of collection, and the beekeeper on the main physicochemical quality parameters (hydroxymethylfurfural "HMF, " moisture, and colour), measured on reception of the raw honey. 1593 samples (11 types of honey categorized by means of pollinic analysis), provided by 98 beekeepers, from 2009 to 2013, were analyzed. Colour was the parameter most affected by the type of honey and year, whereas HMF was the least affected in both cases. The clearest honeys were found to have the greatest moisture (orange, rosemary, and lemon) and the darkest had the least moisture (lavender stoechas, eucalyptus, sunflower, honeydew and retama). Lavender, polyfloral, and thyme had intermediate values of these parameters. For moisture, most samples were in accordance with international requirements (less than 20 g/100 g). All values were below the required limit for HMF (40 mg/kg), although a few of them were abnormally high as they were raw honeys (i.e., 2% of the samples had values higher than 20 mg/kg). The fact that all the inadequate samples came from specific beekeepers highlights the importance of their role, suggesting that training in good practices is the key to guarantee honey quality before it reaches the industry.